Menelaah Multi Wajah Teori Pembangunan dan Sintesisnya dengan Teologi Publik - Mawikere, Marde Christian Stenly; Sambeta, Jenie Aurensia Clara (Institut Agama Kristen Negeri Tarutung, 2024)
This article discusses the evolution of Modernization Theory and Dependency Theory in the context of development theory, with an emphasis on their general contributions in the field of public theology. Through qualitative research, literature review, and content analysis approaches, this study focuses on the distribution of resources, inequality, and the role of theological values or religious teachings in development. The research findings indicate that development theory provides both practical and theological foundations for sustainable social change. A dialectical approach is employed to synthesize concepts from both development theory and public theology, revealing their mutual complementarity. These findings underscore the contribution of development theory in understanding the role of theological values in social development, paving the way for further research in the field of public theology. The synthesis between development theory and public theology is expected to form a strong foundation for development planning that not only focuses on material growth but also on the holistic well-being of humanity, encompassing a comprehensive transformation.